Management of a Previously Failed Root Perforation Repair with Geristore and Deepithelialized Gingival Graft: A 5-Year Follow-Up Case Report - Talal M. Zahid (Case Reports in Dentistry)
Iatrogenic root perforation presents a significant management challenge for clinicians as it may seriously harm the periodontium. More specifically, perforations occurring relative to the crestal bone have a poor prognosis even after repair due to their proximity to the gingival tissues. The current literature reports the use of various materials for root perforation repair including calcium hydroxide, glass ionomer cement, amalgam, and mineral trioxide aggregate (MTA), to name a few. This case report describes the clinical management of a cervical perforation that occurred on the maxillary central incisor. The perforated area was initially repaired with MTA but failed after one year, which resulted in an active lesion at the midlabial aspect of the tooth. The case was subsequently treated using a resin-modified glass ionomer cement (Geristore®) and deepithelialized free gingival graft (DGG). There were favorable clinical and radiographic outcomes at 1-, 3-, and 5-year follow-up. The use of DGG, however, led to some late complications such as gingival cul-de-sac and color discrepancy, which were later resolved with gingivoplasty and frenectomy. We thus conclude that Geristore® has the potential to be a better repair material than the existing ones for crestal and subcrestal root perforations.